Pendidikan Seks Melalui Peer Counselor Terhadap Pengetahuan Remaja Tentang Seks Pranikah - Ni Luh Putu Yuni Krismayanti; Trisno Agung Wibowo; Nining Tunggal Sri Sunarti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Indonesia has 40% of teens who have friends that have had premarital sexual intercourse and 66% of teenagers have a friend who is pregnant out of wedlock. Yogyakarta there are 97.05% of teenagers are not virgins. Bantul there were 113 early marriage, 90% caused by pregnancy out of wedlock. Target sex education in SMK Muhammadiyah Kretek because 80% of students have less knowledge about premarital sex. This incident shows that the figure of an issue.Objective: To determine the influence of sex education through peer counselor towards the youth knowledge about premarital sex in SMK Muhammadiyah Kretek.Methods: This study by Quasi-experiment with one group pretes-posttest design. Sampling purposive of the total respondents 64 students. Types of primary data with survey instruments form questionnaire. Paired data analysis of test samples T-test.Results: Mean knowledge before being given sex education by peer counselor is 74.88 with SD 5.21 and the average level of knowledge when given sex education by peer counselor is 82.00 with SD size 8.52 7.12 results in an improvement of the SD as large as 6.81. Analysis with Paired sample t-test obtained p value 0.000.Conclusion: The influence of sex education through peer counselor for teens about premarital sex knowledge in SMK Muhammadiyah Kretek Year 2013, and statistically meaningful.Keywords: peer couselor, sex education, premarital sex